Long-term yak-grazing alters the plant fine-root resource acquisition strategies in Tibetan alpine meadow - Haiyang Gong; Tserang Donko Mipam; Josep Peñuelas; Jordi Sardans; Youcun Suo; Nan Jia; Heng Huang; Wei Wang; Qingping Zhou; Zhiqiang Wang (Ecological Indicators)
Understanding how fine-root resource acquisition strategies respond to yak grazing is critical for comprehending the structure and functioning of alpine meadow ecosystems. However, the impact of varying intensities of yak grazing on these strategies remains unclear. We utilized a 9-year yak grazing intensity experiment comprising un-grazing, lightly grazing, moderately grazing, and heavily grazing treatments to analyze eight fine-root morphological and chemical traits across three dominant species: Saussurea japonica, Kobresia pygmaea, and Elymus nutans. Our findings revealed that all grazing intensities significantly (p < 0.05) increased specific root length (SRL) and specific root area (SRA), while decreasing root average diameter (RAD) across all three species. Compared with un-grazing treatment, root carbon content (RCC) showed a weak increase (p > 0.05), while root tissue density (RTD) exhibited minor variations under different grazing intensity. Grazing intensity significantly influenced the fine-root resource acquisition strategies for each species, with a transition from an “outsourcing” of resource uptake to mycorrhizal fungi to a “do-it-yourself” resource uptake strategy accompanying increasing grazing intensity. Additionally, our results indicated that grazing intensity indirectly influences morphological and chemical traits of fine roots via altering soil properties and aboveground biomass. Overall, our results provide new evidence that long-term yak grazing modifies the fine-root resource acquisition strategies in alpine meadow ecosystems, enhancing our understanding of plant ecological responses to anthropogenic activities.